Hands-on defibrillation and electrocardiogram artefact filtering technology increases chest compression fraction and decreases peri-shock pause duration in a simulation model of cardiac arrest. Issue 4 (26th November 2015) - Fernando, Shannon M.; Cheskes, Sheldon; Howes, Daniel
Abstract: Background: Reducing pauses during cardiopulmonary resuscitation (CPR) compressions result in better outcomes in cardiac arrest. Artefact filtering technology (AFT) gives rescuers the opportunity to visualize the underlying electrocardiogram (ECG) rhythm during chest compressions, and reduces the pauses that occur before and after delivering a shock. We conducted a simulation study to measure the reduction of peri-shock pause and impact on chest compression fraction (CCF) through AFT. Methods: In a simulator setting, participants were given a standardized cardiac arrest scenario and were randomly assigned to perform CPR/defibrillation using the protocol from one of three experimental arms: 1) Standard of Care (pauses for rhythm analysis and shock delivery); 2) AFT (no pauses for rhythm analysis, but a pause for defibrillation); or 3) AFT with hands-on defibrillation (no pauses for rhythm analysis or defibrillation). The primary outcomes were CCF and peri-shock pause duration, with secondary outcomes of pre- and post-shock pause duration. Results: AFT with hands-on defibrillation was found to have the highest CCF (86.4%), as compared to AFT alone (83.8%, p <0.001), and both groups significantly improved CCF in comparison with the Standard of Care (76.7%, p <0.001). AFT with hands-on defibrillation was associated with a reduced peri-shock pause (2.6 seconds) as compared to AFT alone (5.3 seconds, p <0.001), and the Standard of Care (7.4 seconds, p <0.001). Conclusions: In this cardiac arrest model, AFT results in a greater CCF by reducing peri-shock pause duration. There is also a small but detectable improvement in CCF with the addition of hands-on defibrillation. Résumé: Contexte: La diminution du nombre de pauses durant les manœuvres de réanimation cardiopulmonaire (RCP) donne de meilleurs résultats dans le contexte de l'arrêt cardiaque. La technique de filtrage des parasites (TFP) permet aux secouristes de visualiser, à l'ECG, le rythme cardiaque sous-jacent durant les compressions thoraciques, et réduit ainsi le nombre de pauses avant et après les décharges électriques. L'étude en simulation visait à mesurer la réduction des pauses qui précèdent et suivent les chocs ainsi que leur incidence sur la fraction des compressions thoraciques (FCT), et ce, à l'aide de la TFP. Méthode: Les participants à l'étude ont été placés, dans un contexte de simulation, devant un scénario uniforme d'arrêt cardiaque, puis on leur a demandé, après répartition au hasard, de procéder à la RCP et à la défibrillation selon l'un des trois protocoles expérimentaux suivants: 1) les « soins habituels » (pauses pour l'analyse du rythme et pauses pour les chocs); 2) la TFP seule (pas de pause pour l'analyse du rythme mais pause pour la défibrillation); 3) la TFP avec défibrillation et compressions thoraciques continues (CTC) (pas de pause pour l'analyse du rythme ni pour la défibrillation). Les principaux critères d'évaluation étaient la FCT et la durée des pauses précédant et suivant les chocs, et les critères secondaires d'évaluation consistaient en la mesure de la durée des pauses avant et après les chocs. Résultats: La TFP alliée à la défibrillation et aux CTC a produit une FCT plus élevée (86, 4 %) que la TFP seule (83, 8 %; p <0, 001), et dans les deux groupes il y a eu une amélioration importante de la FCT comparativement aux soins habituels (76, 7 %; p <0, 001). En outre, la TFP alliée à la défibrillation et aux CTC a été associée à une diminution des pauses précédant et suivant les chocs (2, 6 s) par rapport à la TFP seule (5, 3 s; p <0, 001) et aux soins habituels (7, 4 s, p <0, 001). Conclusions: Dans le modèle d'arrêt cardiaque décrit ici, la TFP a permis d'augmenter la FCT par une diminution de la durée des pauses qui précèdent et suivent les chocs. De plus, l'association des CTC et de la défibrillation s'est traduite par une amélioration certes faible mais détectable de la FCT.